PENGARUH EARNING PER SHARE, DEBT TO EQUITY RASIO, DAN RETURN ON ASET TERHADAP HARGA SAHAM (Studi Kasus Pada Perusahaan Energi, Telekomunikasi dan Transportasi yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017) (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to test and analyze the effect of Earning Per share, Debt to Equity Ratio, Return On Equity and Return On Asset to Stock Prices. This study uses Explanative Research. The selection of this research sample uses the Purposive Sampling method using several criteria. From these criteria, 3 energy companies, 3 telecommunications and 5 transportation companies were listed on the Indonesia Stock Exchange for the 2015-2017 period. Analysis of the data used is multiple linear regression analysis and using SPSS version 16. The results of this study indicate that Earning Per Share has no significant positive effect on stock prices. Debt to Equity Ratio has a significant negative effect on stock prices. Return On Equity has a positive but not significant effect on stock prices. Return On Assets has no significant positive effect on stock prices. Keywords: Earning Per Share, Debt to Equity Ratio, Return On Equity, Return On Asset and Stock Price.